Evaluation of single cross maize hybrids during the spring season in Khairahani, Chitwan, Nepal - Khushubu Rai; Oshna Kulung; Sudha Bhandari; Himani Gautam Singh; Mahendra Tripathi (Future Science, 2022)
The experiment was conducted at Khairahani-5, Chitwan, Nepal from 28th February to 20th June 2021. Twenty single cross maize hybrids were evaluated for quantitative and qualitative traits. The experiment was conducted in a randomized complete block design (RCBD) with three replications. Data were recorded on flowering traits, physiological and disease traits, agro-morphological traits, and yield and yield contributing traits. Analysis of variance showed significant differences in all traits except for root lodging, the number of plants per hectare, leaf senescence, and plant aspect. The result indicated that HGABS2-15-2-1B/RL174 had the shortest days to anthesis and silking. The genotype RML138/RML140 was found to have double cob. The longest cob was found in RML76/RML146 (17.3 cm), while the highest cob diameter was found in the Shrestha (5.1cm). The maximum number of grains per row was obtained from RML57/RL174, while the highest thousand-grain weight was obtained in RAMPUR HYBRID-10. Shrestha variety produced highest grain yield (9.954tha-1) followed by RML191/RML18 (9.41tha-1), CAH1715 (9.356tha-1) and RML4/RL111 (9.021tha-1). The traits with the highest broad-sense heritability were the number of rows per ear (79%), days to fifty percent silking (75%), days to fifty percent anthesis (72%), thousand-grain weight (70%), and grain yield (68%). Correlation studies suggested that the number of ears per hectare, cob length, and thousand-grain weight showed a positive and significant correlation with grain yield. Therefore, RML191/RML18, CAH1715, and RML4/RL111 showed better performance in terms of grain yield.